TECHNOLOGICAL INNOVATION IN PUBLIC FINANCIAL GOVERNANCE: A PUBLIC ECONOMIC PERSPECTIVE ON FISCAL EFFICIENCY AND TRANSPARENCY - Fadillah Harmi; Revi Haryanti; Rayhan Agustin; Boni Saputra (Yayasan Amanah Nur Aman, 2026)
Digital innovation in public financial management is one of the key drivers to achieve transparent, efficient, and fair fiscal governance. The purpose of this study is to analyze the application of digitalization in public financial management by studying best practices that have been implemented in Indonesia and around the world. The research method used is a literature study through the analysis of journals, books, and policy documents related to the subject. The results of the study show that the distribution of digital technologies, such as e-budgeting, e-audit, blockchain, and digital payment, reduce potential deviations in the field of moral guidelines, accelerate the public service process, and strengthen fiscal justice through budget equity. This article concludes that digital innovation must be supported by strengthening regulations, increasing the capacity of the apparatus, and public participation so that the goals of good governance can be achieved.